PERAN ILUSTRASI VISUAL DALAM PEMBELAJARAN - Prasetyo, Eko Budi (MAJALAH ILMIAH PEMBELAJARAN, 2006)
Visual Illustration role which is on generally in the form of two dimension have is sufficiently long realized of vital importance. Book of many exploiting in addition clarification from text to submit the message learn. That way the things of with the process evaluate the result learn, there is visual illustration is which as described in an item tes.But that way visual illustration exploiting in study still tend to as supporter and less planned maturedly. This matter is cekup concern because experience symptom learn which verbalistik have enough worry. Is more than anything else added with the wrong symptom of perception ( missperception) also many expressedIn technological era of communications have sophisticated progressively, have appropriately visual illustration role which is on time then place as supporter of communications verbal will be improved to forge the especial role in course of good communications in instructional activity and or at education activity in general